Frontolimbic responses to emotional faces in young people at familial risk of depression - Mannie, Z; Taylor, M; Harmer, C; Cowen, P; Norbury, R (Elsevier, 2011)
Background: The processing of aversive stimuli in patients with major depression is associated with increased neural activity in limbic areas while the activity in cortical regulatory regions is diminished. The aim of the present study was to examine whether related neural abnormalities might be present in young people at increased familial risk of depression but with no personal history of illness. Methods: We used a block designed functional magnetic resonance imaging to measure the neural responses to a task involving the matching of emotional facial expressions in 29 young people (age 16-21 years) who had a biological parent with a history of major depression, and 30 age- and gender-matched controls. Results: Relative to the controls, the participants with increased familial risk of depression (FH) had diminished responses in left dorsolateral prefrontal cortex (DLPFC) to the presentation of fearful faces while the activity in the amygdala did not distinguish the groups. Limitations: FH participants had more depressive symptomatology than did the controls. Their FH status was based on self-report. Conclusions: Young people at increased familial risk of depression show evidence of decreased cortical regulation of aversive stimuli. Further studies will be needed to ascertain if this abnormality might predispose to the eventual development of clinical depression.